2019
DOI: 10.14203/ann.bogor.2019.v23.n1.13-19
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and molecular characterization of newly isolated microalgae strain Chlorella volutis LIPI13-WKT066 from Wakatobi Islands and its potential use

Abstract: Morphology and molecular characterization of microalgae isolated from Wakatobi Marine National Park was conducted. An understanding of the characteristics of morphology, molecular, as well as metabolites profile of the microalgae species is potentially useful for its future application. The primary aim of this study was to isolate, identify and characterize the microalgae strain isolated from Wakatobi Marine National Park labeled as LIPI13-WKT066 with the emphasis on the evaluation of amino acid content as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The phylogenetic tree also better understands the taxonomy and describes the evolutionary lineage of species, organisms, or one distinct ancestor. Rahman et al (2019) conducted a phylogenetic analysis of microalgae isolated from Wakatobi Marine National Park, Indonesia. The BLAST result of 18S DNA sequences showed that the isolated microalgae strain was closest to Chlorella sp.…”
Section: Phylogenetic Tree Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic tree also better understands the taxonomy and describes the evolutionary lineage of species, organisms, or one distinct ancestor. Rahman et al (2019) conducted a phylogenetic analysis of microalgae isolated from Wakatobi Marine National Park, Indonesia. The BLAST result of 18S DNA sequences showed that the isolated microalgae strain was closest to Chlorella sp.…”
Section: Phylogenetic Tree Analysismentioning
confidence: 99%
“…Over 60% of Indonesia's territory is covered by water (Rahman et al, 2019). To be one of the enormous diversities in the world, not all of those areas had been explored yet.…”
Section: Introductionmentioning
confidence: 99%